Sonate pour le pianoforte : oeuv. 106 ... composeé et dédiée à son altesse Monseigneur l'Archiduc Rodolphe d'Autriche Cardinal et Price Archeveque d'Olmütz etc. par Louis van Beethoven - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Hamburg; Jean Aug. Böhme; Germany, 2022)
Edition of the Piano Sonata no. 29 in B-flat major, op. 106, published in an unnamed series by Jean Aug. Böhme in Hamburg. With decorative passé-partout title page. Plate number 867.